Upaya Pengentasan Kemiskinan Masyarakat Muslim Papua Melalui Inklusi Keuangan (Studi Pada BMT KUM 3 dan BMT Al-Hijrah) - Faizah, Nur (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to determine the implementation of the inclusion program by BMTs in Sorong (BMT Al-Hijrah and BMT KUM 3) to alleviate poverty in the Papuan Muslim community. This study uses descriptive qualitative research methods. The technique for collecting data is the interview, observation, and documentation. The data analysis technique used descriptive analysis with the stages of data reduction, data presentation, and conclusions. The results of this study are BMT KUM 3 and BMT Al-Hijrah have implemented financial inclusion programs to alleviate poverty in the Papuan Muslim community. In addition, the efforts that have been made by the two BMTs are by providing easy access for the poor to reach, besides that the two BMTs provide pick-up services, as well as facilitating the requirements for collection and financing products, and provide fast ones. The obstacles BMT KUM 3 and Al-Hijrah face are, First, internal factors, namely the lack of human resources, and external factors, namely customers do not have collateral. Second, from the perception of the Papuan Muslim community who are not familiar with BMT and feel the need for financial services provided by BMT.